Acoustic, dielectric and piezoelectric properties of 1-3 connectivity barium titanate-portland cement composites - Rattiyakorn Rianyoi (2018)
The 1-3 barium titanate (BT)-Portland cement (PC) Composites were fabricated using dice and fill method for smart materials applications in civil engineering structure. The acoustic, dielectric and piezoelectric properties of composites were studied. The results show that the acoustic impedance of the composites can be tailored to match that of the host structure, concrete. Moreover, the dielectric constant (εr) and piezoelectric coefficients (d 33) of the composites increased with the increase of BT volume content. The d 33values were found to be 63 pC/N and 128 pC/N for composites with BT volume content of 30% and 70%, respectively. Therefore, this new kind of lead-free piezoelectric ceramic-Portland cement composite has potential to be used for smart structure in the civil engineering field. © 2013 Copyright Taylor and Francis Group, LLC.